Engineering Halomonas bluephagenesis TD01 for non-sterile production of poly(3-hydroxybutyrate-co-4-hydroxybutyrate). (November 2017) - Chen, Xiangbin; Yin, Jin; Ye, Jianwen; Zhang, Haoqian; Che, Xuemei; Ma, Yiming; Li, Mengyi; Wu, Lin-Ping; Chen, Guo-Qiang
Graphical abstract: Highlights: Halomonas bluephagenesis TD01 was engineered for P(3HB- co -4HB) production. Gene orfZ encoding 4HB-CoA transferase was integrated into the chromosome. 70–80 g/L cell biomass with >60% P(3HB- co -16 mol% 4HB) were obtained in fermentors. The non-sterile fermentations were scaled up from 1, 7 to 1000-L with similar results. P(3HB- co -16 mol% 4HB) showed good elasticity with over 1000% elongation at break. Abstract: Poly(3-hydroxybutyrate- co -4-hydroxybutyrate), short as P(3HB- co -4HB), was successfully produced by engineered Halomonas bluephagenesis TD01 grown in glucose and γ-butyrolactone under open non-sterile conditions. Gene orfZ encoding 4HB-CoA transferase of Clostridium kluyveri was integrated into the genome to achieve P(3HB- co -4HB) accumulation comparable to that of strains encoding orfZ on plasmids. Fed-batch cultivations conducted in 1-L and 7-L fermentors, respectively, resulted in over 70 g/L cell dry weight (CDW) containing 63% P(3HB- co -12 mol% 4HB) after 48 h under non-sterile conditions. The processes were further scaled up in a 1000-L pilot fermentor to reach 83 g/L CDW containing 61% P(3HB- co -16 mol% 4HB) in 48 h, with a productivity of 1.04 g/L/h, again, under non-sterile conditions. The elastic P(3HB- co -16 mol% 4HB) shows an elongation at break of 1022 ± 43%. Results demonstrate that the engineered Halomonas bluephagenesis TD01 is a suitable industrial strain for large scale production under open non-sterile conditions.